Improving the phase stability of inorganic lead halide perovskites through K/Rb doping. (1st May 2019) - Wang, Si-Qin; Shen, Shiyu; Xue, Xiong-Xiong; He, Yunqiu; Xu, Zheng-Wei; Chen, Keqiu; Feng, Yexin
Abstract: All-inorganic perovskites have gained considerable significance. Despite their superior thermal robustness, poor phase stability has rendered inorganic perovskites adverse. Herein, on the basis of first-principles calculations, we find that the incorporation of rubidium (Rb) and potassium (K) in an appropriate ratio will stabilize CsPbI2 Br perovskites considerably, in which the cooperative interactions between Rb/K, I and Br play an important role. Besides, it is verified that 2D orthorhombic CsPbI3 with a thickness of ∼1 nm exhibits outstanding stability, even exceeding the non-perovskite, yellow structure and has a suitable band gap for solar cell applications.